Novel PHEMA Nanoparticles for Controlled Drug Delivery: Synthesis, Characterization, and Potential Applications - Begam, Huda; Bajpai, A.K. (Chemical and Materials Sciences: Research Findings Vol. 3, 2025)
This chapter discusses the preparation and characterization of poly (2-hydroxyethyl methacrylate) (PHEMA) nanoparticles for potential use in controlled drug delivery. PHEMA nanoparticles were prepared using a modified suspension polymerization technique. This study describes the preparation, identification, and structural and morphological characterization of PHEMA nanoparticles. PHEMA nanoparticles have been characterized using Fourier Transform Infrared Spectroscopy (FTIR), scanning electron microscopy (SEM), and particle size analysis. FTIR is used to confirm the presence of specific functional groups within the PHEMA structure, while particle size distribution provides information about the dimensions and uniformity of the nanoparticles. It is found that the nanoparticles have having size of up to 100 nm and are almost identical in shape. The small size of nanoparticles makes them a suitable candidate for biomedical and pharmaceutical applications, especially in the controlled drug delivery field. PHEMA nanoparticles can encapsulate and release drugs, making them effective for targeted drug delivery, such as in cancer therapy. PHEMA nanoparticles are significant in biomedical applications due to their biocompatibility, tenable properties, and ability to serve as drug-delivery vehicles. Their high water content, low toxicity, and tissue compatibility make them suitable for a variety of medical devices and therapies, including soft contact lenses, drug delivery systems, and tissue regeneration scaffolds.